Salvage of necrotic flap following malignant peripheral nerve sheath tumor excision using multimodal pharmacotherapy: a case report - Chen, Lili; Wu, Xiangyi; Li, Feng (Frontiers in Oncology, 2025)
A 73-year-old man presented with a 20-year history of a mass in the right scapular region that had rapidly enlarged and become painful. Initially misdiagnosed as an infected sebaceous cyst, intraoperative findings revealed a solid, poorly demarcated mass. Histopathology confirmed malignant transformation of a neurofibroma into a high-grade malignant peripheral nerve sheath tumor, with positive margins. The patient underwent wide local excision with frozen-section–verified clear margins and full-thickness back flap reconstruction. On postoperative day 3, the flap developed progressive ischemic necrosis. Salvage was achieved using a novel combination of topical papaverine hydrochloride, Danhong injection, and enzymatic debridement, leading to full revascularization by day 9. The patient was discharged in stable condition on day 15. This case underscores the need for early pathological evaluation of rapidly enlarging skin masses when clinical and imaging findings are discordant. It also demonstrates the successful use of papaverine, Danhong, and enzymatic debridement as a salvage strategy for postoperative flap necrosis.